Loss of membranous expression of the intracellular domain of EpCAM is a frequent event and predicts poor survival in patients with pancreatic cancer. Issue 5 (2nd December 2013) - Fong, Dominic; Moser, Patrizia; Kasal, Armin; Seeber, Andreas; Gastl, Guenther; Martowicz, Agnieszka; Wurm, Martin; Mian, Christine; Obrist, Peter; Mazzoleni, Guido; Spizzo, Gilbert
<x xml:space="preserve">Abstract</x> Aims Epithelial cell adhesion molecule (EpCAM) is a widely used immunohistochemical marker for epithelial human malignancies. Antibodies to target EpCAM are usually directed against its ectodomain (EpEX), but do not detect the intracellular domain (EpICD). The aim of this study was to compare membranous EpEX versus EpICD expression by immunohistochemistry. Methods and results Concurrent EpEX and EpICD expression was investigated retrospectively in cancerous and matched non‐neoplastic tissue samples from patients with pancreatic adenocarcinoma. In total, 317 paired samples of pancreatic tissue from 88 patients were analysed and correlated with clinicopathological parameters. In non‐cancerous tissue, a high concordance of membranous EpEX and EpICD expression was observed and defined as the expression of the full‐length EpCAM (EpEX+/EpICD+ phenotype, EpCAMMF), which was highly predominant. In contrast, while most tumour samples were EpEX positive, loss of membranous EpICD expression (EpEX+/EpICD− phenotype, EpCAMMT) was observed in one‐third of cases, and these patients had a significantly shortened disease‐free and overall survival. Conclusions This study demonstrates for the first time that loss of membranous EpICD expression is a frequent event and predicts poor prognosis in patients with pancreatic cancer. Additional studies evaluating the predictive and prognostic value of the expression of different membranous EpCAM variants are warranted in epithelial cancers.